If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8x + -2x) = 32 Combine like terms: 8x + -2x = 6x -1(6x) = 32 Remove parenthesis around (6x) -1 * 6x = 32 Multiply -1 * 6 -6x = 32 Solving -6x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = -5.333333333 Simplifying x = -5.333333333
| 3(x+2)+2x=2(x-7)+2x+5 | | 12y-32=-15 | | 82-(-3)= | | 12y-32=-35 | | -21-(-24)= | | x-24=2x+5 | | 8n^2=24n | | 6x+9=-72-6x | | 24*6x=9-9x | | n^2+w=12 | | x-3.75=12.25 | | z=2x-7y | | 6(x+31)=216 | | 1/3p=12 | | 5x=1+2y | | -x+8=6 | | X/2-4-6 | | 10x-68=-8 | | 6(2/3x-10) | | 7x-4=22-x | | 10+4x=4+x | | -7x-9=-30 | | -6x+9=-3 | | (2y-3)(3y+5)= | | 2x+5=7 | | 102-7x=11x+20 | | 12y-10=3x+2 | | 5x+191=15x-9 | | x^5+64x=0 | | 7-(3x-1)=91 | | 7b-6(1-2b)=10 | | 2p+8g=360 |